PENGARUH MUTAGEN KIMIA SODIUM AZIDA TERHADAP MORFOLOGI TANAMAN CABAI BESAR (Capsicum annuum L.) - Yunita Sari, Ni Kadek; Pharmawati, Made; Junitha, I Ketut (Metamorfosa: Journal of Biological Sciences, 2013)
The aim of this research was to examine the effects of sodium azide at concentration of 1 mM, 2 mM, 3 mM, 4 mM and 5 mM on the morphological characters of Capsicum annuum L. The method used for the observation of morphological characters was direct observation by measuring plant height, leaf length and width as well as counting the number of leaves. The results showed that effect of sodium azide at 3 mM caused an increase in plant height, while concentration of 1 mM, 2 mM, 4 mM dan 5 mM caused a decrease in plant height. Similar trends were found for number of leaf. Leaf length and width tended to increase in sodium azide treatments.
Keywords: Capsicum annum, sodium azide, morphology.